Determining carotid plaque vulnerability using ultrasound center frequency shifts. (March 2016) - Erlöv, Tobias; Cinthio, Magnus; Edsfeldt, Andreas; Segstedt, Simon; Dias, Nuno; Nilsson, Jan; Gonçalves, Isabel
Abstract: Background: The leading cause of morbidity and mortality worldwide is atherosclerotic cardiovascular disease, most commonly caused by rupture of a high-risk plaque and subsequent thrombosis resulting in stroke, myocardial infarction or sudden death depending on the affected arterial territory. Accurate, non-invasive methods to identify such lesions known as vulnerable or high-risk plaques are currently sub-optimal. Our aim was to validate a new non-invasive ultrasound method to identify high-risk carotid plaques. Methods: We evaluated a new method based on the center frequency shift (CFS) of the ultrasound radio frequency data obtained from carotid plaques compared to a reference phantom. We evaluated the method both ex vivo, on 157 sections from 18 plaques, and in vivo, in 39 patients 1-day prior to carotid plaque removal, and correlated the data with histology. Results: The CFS correlated with a plaque vulnerability index based on histological areas stained for lipids, macrophages, hemorrhage, smooth muscle cells and collagen (r = −0.726, P = 1.7 × 10 −8 ). Plaques with CFS below median had larger cores, more macrophages and were less rich in collagen in agreement with the definition of rupture-prone plaques. The accuracy to detect plaques with high vulnerability index was 78% (confidence interval (CI) 61–89%), with sensitivity 77% (CI 61–89%) and specificity 78% (CI 62–89%). Conclusions: Our method is the first to characterize atherosclerotic plaque components that affect plaque vulnerability using CFS. Highlights: An ultrasound method for assessing carotid plaque vulnerability is proposed. The method is based on shifts in ultrasound center frequency caused by tissue. The center frequency shift is related to carotid plaque vulnerability.